Characteristics of patients with multiple arterial aneurysms: a retrospective cross-sectional observational study - Körfer, Daniel; Erhart, Philipp; Wortmann, Markus; Dihlmann, Susanne; Grond-Ginsbach, Caspar; Kilian, Samuel; Asatryan, Ara; Jung, Georg; Schmitz-Rixen, Thomas; Böckler, Dittmar; Hakimi, Maani (Vasa, 2023)
Summary:Background: The aim of this retrospective cross-sectional observational study was to determine differences of patients with multiple arterial aneurysms to patients with single arterial aneurysms. Patients and methods: Patients with the diagnosis of an arterial aneurysm from January 2006 to January 2016 in the department of vascular surgery Heidelberg were investigated. Excluded were patients with hereditary disorders of connective tissue or systemic inflammatory disease, as well as other arterial pathologies than true aneurysms. Patients with multiple aneurysms (defined by at least four aneurysms) were compared to patients with single aneurysms concerning age at initial diagnosis, sex and affected arterial site. To verify the findings, a replication of the study was performed at a comparable institution. Results: Of 3107 patients with arterial aneurysms, 918 were excluded. Of the resulting 2189 patients, 1238 (56.6%) patients had a single, 808 (36.9%) two or three, and 143 (6.5%) at least four aneurysms (group mult-AA). Nine hundred seventy-two patients (44.4%) had a single abdominal aortic aneurysm (group sing-AAA). Age at initial diagnosis differed between mult-AA (66.7±9.5 y) and sing-AAA (69.1±8.6 y) (p=0.0338). Within mult-AA, 138 patients (96.5%) were male, compared with 865 patients (89.0%) in sing-AAA (p=0.0041). The most frequent aneurysm localization shifted from the abdominal aorta and its branches in patients with a single aneurysm (n=1029; 83.1%) to pelvic and leg arteries in patients with at least four aneurysms (n=318; 63.2%). The replication of the study at the department of vascular surgery Frankfurt confirmed the younger age at initial diagnosis in mult-AA (67.3±12.5 y) compared to sing-AAA (70.9±9.6 y) (p=0.0259) and the distribution shift toward the arteries below the aortic bifurcation in mult-AA. Conclusions: Patients with multiple aneurysms are younger at initial diagnosis and differ concerning aneurysm localization compared to patients with a single aneurysm.
Online veröffentlicht: 5. Januar 2023
Gesehen am 29.01.2024